THE REMIX PHENOMENON AND THE NEED TO REFORM INDONESIAN COPYRIGHT LAW - Harsa Wahyu Ramadhan (PRANATA HUKUM, 2022)
The problem in this research is The rapid development of computer technology in the 20th century has encouraged the emergence of the remix phenomenon in society. Remix can be done through the use of computer technology for works/creations that are rearranged, combined and remixed to produce new works. Remix seems to be a new phenomenon, even though historically this practice is actually not a new thing and the extent to which copyright law reform is needed. Can this Copyright Act synergize with the legal structure and culture of Indonesian society in order to create a legal system that can produce justice, benefit, and legal certainty? How copyright enforcement on computer software can create effective legal protection